Virtual Reality Based Gaze-Sensitive Aiming Task Platform: Role of Attention Allocation in Task Performance for Individuals With Autism and Typically Developing Individuals - Dharma Rane; Prachi Sharma; Madhu Singh; Uttama Lahiri (IEEE, 2023)
Individuals with Autism Spectrum Disorder (ASD) often exhibit difficulty in movement preparation and allocating attention towards different Regions of Interest (ROIs) of a visual stimulus. Though research has alluded to differences in movement preparation for aiming tasks between individuals with ASD and typically developing (TD) individuals, there is limited evidence (true for near-aiming tasks) on the contribution of the window (i.e., time duration) of movement preparation (i.e., the planning window preceding movement initiation) on one’s aiming performance. However, investigation of the contribution of this planning window on one’s performance in far-aiming task remains as majorly unexplored. Again, often one’s eye movement leads the initiation of hand movement (for task execution) indicating the importance of monitoring one’s eye movement in the planning stage, critical for far-aiming task. Most of the studies (in conventional settings) examining the role of gaze behavior on aiming performance have involved TD individuals and only a few involving individuals with ASD. Here, we have designed Virtual Reality (VR)-based Gaze-sensitive far-aiming (dart throw) task and monitored the looking pattern of participants while they interacted with the task environment. We carried out a study with 40 participants (20 in each of ASD and TD groups) to understand how the participant groups differed in task performance and gaze fixation within the movement planning window. We observed difference in the scan path and last fixation within the movement planning window before triggering the release of the dart with relevance to task performance.